Tracking 6 weeks of training/surfing sessions of adolescent competitive surfers: just what are these young surfers up to? - Farley, O. R. L.; Secomb, J. L.; Parsonage, J.; Lundgren, L.; Abbiss, C.; Sheppard, J. M. (Journal of Australian Strength and Conditioning, 2015)
Limited research has investigated the duration adolescent competitive surfers spend free surfing, competing, being coached and spend physically training in terms of strength, balance and conditioning. It has been previously documented that surfers can spend between 3.7 - 5 hours a day practicing in good surf conditions, 3-5 days a week for recreational and international level surfers (1-3). Within juniors (>19 y), weekly surfing hours range between 7.5 (Recreational) and 18.1 (Competitive) hours surfing each week (4). Previous research within other sports has reported the weekly training hours to be approximately 4-6.7 hours for U14-U15 age groups, and 9-10 hours for U17 soccer players (5, 6). Furthermore, rugby union has reported approximately 15 hours of weekly training (7, 8), pre pubertal female gymnasts 14 hours (9), and triathlon approximately 16 hours (10). In terms of land-based training, surfers participate in minimal training sessions with an average of 0-2 sessions per week) (4, 11) with majority of a surfer`s training regime undertaken in the water (1). In comparison, field sports strength training in soccer for both U15 and 17 is approximately 0.90 mins per week (6), and 6 hours in rugby per week (12), and swimmers 2-3 times per week.